THE REPRESENTATION OF INDEPENDENT WOMEN IN WARDAH ADVERTISEMENT: A STUDY OF SEMIOTIC BY PIERCE - Rachmadina Maghfira; R. Myrna Nur Sakinah; Dadan Rusmana (Universitas Sebelas Maret, 2022)
Advertisement is a tool to build the communication with the target or audiences to grab their attention and interest to be intrigue by the persuasive words and diction. The advertisement also defined as an object that has to be analyse more deeper what is actually the advertisement is willing to convey by looking in its sign. Therefore, the researcher uses the theory from Charles Sanders Pierce of semiotic study to figure out the hidden message from all the sign on the object analyses. The researcher use the descriptive qualitatve method to analyse the data. The researcher also use the technique of analyse the data by observing the data, taking notes, reduction the data, presenting the data with diagram and make an inference to get the result of the data analyses. Based from six samples images from Wardah advertisement on their official Instagram account. The result shows that there are 6 data of an icons, 12 data of indexes and 19 data of symbols. The researcher found the fact that the advertisement was not only used for marketing but also to emerging the represntation of independent women through color, and diction used in Wardah advertisement on instagram.